Path Analysis of Campus Walkability/Bikeability and College Students' Physical Activity Attitudes, Behaviors, and Body Mass Index. Issue 3 (March 2018) - Horacek, Tanya M.; Dede Yildirim, E.; Kattelmann, K.; Brown, O.; Byrd-Bredbenner, C.; Colby, S.; Greene, G.; Hoerr, S.; Kidd, T.; Koenings, M. M.; Morrell, J.; Olfert, M. D; et al.
Purpose: The purpose of this study was to assess the relationship between the walkability/bikeability of college campuses and students' body mass index (BMI) with student physical activity (PA) attitudes and behaviors as potential mediators. Design: Cross-sectional. Setting: Thirteen university campuses. Participants: A total of 1384 student participants. Measures: Walkability/bikeability environmental score (ES): 12-item audit assessed an average of 44 path segments per campus. Students were measured for height and weight and completed online surveys. Physical activity stage of change/behavior intentions were assessed using the transtheoretical model. The Cognitive Behavioral Physical Activity Questionnaire assessed outcome expectations, self-regulation, and personal barriers. International Physical Activity Questionnaire assessed walking-, moderate-, and vigorous-intensity PA. Analysis: Descriptive statistics, zero-order correlations, and path analysis with maximum likelihood estimation. Results: The overall model fit was good with χ 2 of 171.388 ( df = 18), P < .001, comparative fit index value of .95, and a root mean square of approximation of .079. After controlling for gender, there was a direct negative association between walkability/bikeability ES and BMI (β = −.085) and positive association between personal barriers and BMI (β = .134). Walkability/bikeability ES was positively associated with walking-intensity PA (β = .010). Self-regulation was positively associated with moderate-intensity PA (β = .213), which, in turn, was negatively associated with BMI (β = −.057). Conclusions: The ease of walking and biking on a campus was related to college students' walking behavior and their BMI. Students' PA behavioral intentions were associated with moderate PA and lower BMI. These results provide evidence to focus on policies and structural supports for walkable/bikeable environments to supplement and enhance interventions encouraging individual behavior change for PA and weight management.